(untitled) (Research, Society and Development, 2020)
This article raises the reflection of the teacher training action in the area of ​​inclusive education directly relates the performance, seeks to debate the importance of this training since the initial training (undergraduate). It engenders the importance of this preparation as a guarantee of a performance that provides these students with equity in educational opportunities and offers, guaranteeing them curricular conditions that go beyond those proposed for curricular adequacy and temporality. With the aim of expanding and ensuring their social participation in their educational environment and not just their “socialization”. We used as a methodology the documentary analysis of the National Curriculum Guidelines for the Undergraduate Course in Pedagogy and the bibliographic review of some authors on the theme of teacher education in the area of ​​inclusive education. After raising this debate on teacher training in undergraduate courses for the performance and the importance of this training in an educational system that seeks to be inclusive, we conclude that we still have a lot to discuss about teacher training in this area.